Bleeding Assessment Scale in Critically Ill Children (BASIC): Physician-Driven Diagnostic Criteria for Bleeding Severity. Issue 12 (December 2019) - Nellis, Marianne E.; Tucci, Marisa; Lacroix, Jacques; Spinella, Philip C.; Haque, Kelly D.; Stock, Arabela; Steiner, Marie E.; Faustino, E. Vincent S.; Zantek, Nicole D.; Davis, Peter J.; Stanworth, Simon J.; Cholette, Jill M.; et al.
Abstract : Objective: Although bleeding frequently occurs in critical illness, no published definition to date describes the severity of bleeding accurately in critically ill children. We sought to develop diagnostic criteria for bleeding severity in critically ill children. Design: Delphi consensus process of multidisciplinary experts in bleeding/hemostasis in critically ill children, followed by prospective cohort study to test internal validity. Setting: PICU. Patients: Children at risk of bleeding in PICUs. Interventions: None. Measurements and Main Results: Twenty-four physicians worldwide (10 on a steering committee and 14 on an expert committee) from disciplines related to bleeding participated in development of a definition for clinically relevant bleeding. A provisional definition was created from 35 descriptors of bleeding. Using a modified online Delphi process and conference calls, the final definition resulted after seven rounds of voting. The Bleeding Assessment Scale in Critically Ill Children definition categorizes bleeding into severe, moderate, and minimal, using organ dysfunction, proportional changes in vital signs, anemia, and quantifiable bleeding. The criteria do not include treatments such as red cell transfusion or surgical interventions performed in response to the bleed. The definition was prospectively applied to 40 critically ill children with 46 distinct bleeding episodes. The kappa statistic between the two observers was 0.74 (95% CI, 0.57–0.91) representing substantial inter-rater reliability. Conclusions: The Bleeding Assessment Scale in Critically Ill Children definition of clinically relevant bleeding severity is the first physician-driven definition applicable for bleeding in critically ill children derived via international expert consensus. The Bleeding Assessment Scale in Critically Ill Children definition includes clear criteria for bleeding severity in critically ill children. We anticipate that it will facilitate clinical communication among pediatric intensivists pertaining to bleeding and serve in the design of future epidemiologic studies if it is validated with patient outcomes.